Software Analytics Platform for Converged Healthcare Technologies. (2016) - Arjun, R.; D'Souza, Sunil C.
Abstract: The purpose of the paper is developing a common software based analytics framework that can be coupled to health devices which monitor health conditions using smart devices, mobile phones, tablets and gadgets. The diverse and heterogeneous sensor data generated can collectively be feed into local home based health information system. These information systems as a large group in cluster model form the basis of backbone networks for governmental health institutions and thereby societal impact as effect of such implementation can be studied as experimental basis of further research.